Peranan Media Sosial Dalam Meningkatkan Minat Berkunjung Wisatawan Di Kota Sabang - Rachman, Intan Cahyani; Indah, Yusmika; Anwar; Raihan, Rahmi (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
One technology that is developing rapidly and is part of communication technology is social media. Among various social media currently available, the three most used social media are Facebook, YouTube and Instagram. Facebook is the first social media that makes people in the world connected to each other and continues to develop its features so that it is difficult for old users to leave it. YouTube is a social media that allows someone to upload videos that they have for a long time. Instagram itself is popular because of its practical and simple way of using it. The aim of this research was to see how big a role social media plays in attracting tourists to visit Sabang City. This research was quantitative descriptive. The research method used was simple linear regression. The independent variable used was social media with the indicator being social media which is often used as promotional media such as Facebook, YouTube and Instagram, while the interest in visiting tourists to Sabang City was used as the dependent variable. The influence of social media in increasing tourist interest in the city of Sabang will be measured using the t test. Data collection was carried out by distributing questionnaires to tourists, both local and foreign. The research results show that the regression equation obtained is Y = 39.832 + 0.716X. The results of the t test show that the t count is 2,883, which means the t count is greater than the t table and shows the influence of social media on tourists' interest in visiting Sabang City. The coefficient of determination produces a figure of 12.7%, which shows that social media has an influence of 12.7% on tourist interest in visiting and the remaining 87.3% is influenced by other factors outside the model.